DNA microarray assay and real‐time PCR as useful tools for studying the respiratory tractMycoplasmapopulations in young dairy calves. Issue 9 (September 2017) - Bottinelli, Marco; Passamonti, Fabrizio; Rampacci, Elisa; Stefanetti, Valentina; Pochiero, Luca; Coletti, Mauro; Rueca, Fabrizio; Hyatt, Doreene R.; Schnee, Christiane
Abstract : Purpose. : With more than 120 species, the genus Mycoplasma is one of the largest taxa in the class Mollicutes, a group of micro‐organisms that are characterized by apparent simplicity and to which important animal pathogens belong. Mycoplasma bovis is the most frequently identified pathogenic Mycoplasma in cattle; however, the prevalence of other Mycoplasma species living in calves' airways is poorly understood. The aim of this work was to characterize the respiratory tract mycoplasma populations in calves on one of the largest dairy farms in Italy using a real‐time PCR assay and a DNA microarray assay. Methodology. : A total of 49 nasal swabs and 49 trans‐tracheal aspirations from non‐vaccinated veal calves were analysed. Genomic DNA was extracted from the samples and then tested using a real‐time PCR targeting the oppD gene of M. bovis and a DNA microarray that was able to identify more than 70 Mycoplasma species. Results. : Forty‐two out of 49 calves tested positive for Mycoplasma spp. (85.7%). None of the samples tested positive for M. bovis . A majority (73.5%) of the 98 samples tested positive for M. dispar, while 8 samples tested positive for M. bovirhinis (8.2%). Conclusion. : Our results expand our knowledge regarding the diversity of Mycoplasma populations in the respiratory airways of very young veal calves and add data regarding M. bovis prevalence in the Italian cattle population. However, the importance of these species in the respiratory diseases of calves still remains to be determined.